PENGUKURAN KINERJA PORTOFOLIO OPTIMAL CAPITAL ASSET PRICING MODEL (CAPM) DAN ARBITRAGE PRICING THEORY (APT) (Studi Kasus : Saham-saham LQ45) - Dedi Baleo Pasaribu; Di Asih I Maruddani; Sugito Sugito (Jurnal Gaussian, 2018)
Investing is placing money or funds in the hope of obtaining additional or specific gains on the money or funds. The capital market is one place to invest in the financial field of interest to investor. This is because the capital market gives investor the freedom to choose securities traded in the capital market in accordance with the wishes of investor. Investor are included in risk averter, that means investor will always try to avoid risk. To avoid risk, investor try to diversify their investment. Diversification concept commonly used is portfolio. To maximize the return to be earned, the investor will invest his funds into several stocks in order to earn a greater profit. Capital Asset Pricing Model (CAPM) is a balance model that describes the relation of a risk with return more simply because it uses only one variable to describe the risk. Arbitrage Pricing Theory (APT) is a balance model that used many risk variables to see the relation of risk and return. With both models will be obtained a portfolio with each constituent stock is four stocks selected from 45 stocks in the LQ45 index. To find out which portfolio is the best performed a performance analysis using the Sharpe index. From the measurement result, it is found that the best portfolio is the CAPM portfolio with composite stock is PTBA with investment weight of 0.467%, BUMI with investment weight of 12.855%, ANTM with investment weight of 53.077% and PPRO with investment weight of 33.601%. Keywords: LQ45, portfolio, Capital Asset Pricing Model (CAPM), Arbitrage Pricing Theory                       (APT), Sharpe Index